2012
DOI: 10.1007/s00253-012-4110-4
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification performance and microbial diversity in a packed-bed bioreactor using PCL as carbon source and biofilm carrier

Abstract: Polycaprolactone (PCL) was used as both carbon source and biofilm support for denitrifying bacteria in a packed-bed bioreactor. The denitrification performance and microbial diversity were investigated. The microbial community of biofilm developed on the surface of PCL in the reactor was analyzed by pyrosequencing method. The experimental results showed the average nitrate removal efficiency reached 93 % at stable operation. ESEM observation and FTIR analysis were conducted to characterize the PCL structure be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Other abundant genera species in this study, such as Gemmata and Porphyrobacter have been observed in drinking water samples and suggested to be adapted to oligotrophic conditions in DWDSs [58][59][60] . In addition, Azospira, which belongs to denitrifying genus 61 , was detected to be abundance as well. Combine with the discussion above, the decrease of nitrate nitrogen in this study could due to the possible occurrence of denitrification process.…”
Section: Discussionmentioning
confidence: 98%
“…Other abundant genera species in this study, such as Gemmata and Porphyrobacter have been observed in drinking water samples and suggested to be adapted to oligotrophic conditions in DWDSs [58][59][60] . In addition, Azospira, which belongs to denitrifying genus 61 , was detected to be abundance as well. Combine with the discussion above, the decrease of nitrate nitrogen in this study could due to the possible occurrence of denitrification process.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, Z-WWTP had higher abundances of Dechloromonas, Nitrospira, and Thauera, while Y-WWTP had higher Nitrosomonas concentrations and lower Nitrospira abundances. Dechloromonas and Thauera were identified as typical denitrifying bacteria in wastewater treatment [30], while Nitrosomonas and Nitrospira were predominant ammonia oxidation bacteria and nitrite oxidation bacteria in WWTPs [31][32][33]. In an SBR process, the Nitrospira population decreased sharply and was ultimately wiped out in the presence of copper [34].…”
Section: Taxonomic Classification Of the Bacterial Communitiesmentioning
confidence: 99%
“…Desulfobacter and Desulfopila were detected in a constructed wetland to which starch/polylactic acid blends were added to support denitrification [103]. Denitratisoma was found capable of complete denitrification of wastewater [104,105]. We observed both Halomonas and Denitratisoma in our reactor, whose frequencies decreased with increasing influent nitrate-N concentration.…”
Section: Microbial Community Structurementioning
confidence: 61%